Exploring the origin of high optical absorption in conjugated polymers - Vezie,M; Few,S; Meager,I; Pieridou,G; Dörling,B; Ashraf,RA; Goñi,AR; Bronstein,H; McCulloch,I; Hayes,SC; Campoy-Quiles,M; Nelson,J (Nature Materials, 2016)
The specific optical absorption of an organic semiconductor is critical to the performance of organic optoelectronic devices. For example, higher light-harvesting efficiency can lead to higher photocurrent in solar cells that are limited by sub-optimal electrical transport. Here, we compare over 40 conjugated polymers, and find that many different chemical structures share an apparent maximum in their extinction coefficients. However, a diketopyrrolopyrrole-thienothiophene copolymer shows remarkably high optical absorption at relatively low photon energies. By investigating its backbone structure and conformation with measurements and quantum chemical calculations, we find that the high optical absorption can be explained by the high persistence length of the polymer. Accordingly, we demonstrate high absorption in other polymers with high theoretical persistence length. Visible light harvesting may be enhanced in other conjugated polymers through judicious design of the structure.